2018
DOI: 10.3390/en11020399
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Agglomerator of Tetra-n-Butyl Ammonium Bromide Hydrate and Its Effect on Hydrate-Based CO2 Capture

Abstract: Tetra-n-butyl ammonium bromide (TBAB) was widely used in the research fields of cold storage and CO 2 hydrate separation due to its high phase change latent heat and thermodynamic promotion for hydrate formation. Agglomeration always occurred in the process of TBAB hydrate generation, which led to the blockage in the pipeline and the separation apparatus. In this work, we screened out a kind of anti-agglomerant that can effectively solve the problem of TBAB hydrate agglomeration. The anti-agglomerant (AA) is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…Zhou et al reported that the maximum solid fraction required to keep a slurry pumpable was about 0.40 in mass fraction . Their conclusion was consistent with the theoretical relationship between the viscosity and solid fraction of the slurry reported by Graham et al The addition of an inhibitor of hydrate formation, such as a surfactant, is effective in suppressing the viscosity of a slurry. Most recently, it was found that adding amino acids to a hydrate slurry reduces its viscosity, thereby reducing the pumping power consumption . Although representative surfactants such as sodium dodecyl sulfate and Span 80, which are not encapsulated in hydrate cages, serve as kinetic promoters for hydrate formation, the phase equilibrium temperature of hydrates undergoes very little change when adding the above surfactants to hydrate formation systems. , Conversely, adding additional guest compounds such as tetrahydropyran alleviate the phase equilibrium conditions …”
Section: Air Conditioningsupporting
confidence: 55%
“…Zhou et al reported that the maximum solid fraction required to keep a slurry pumpable was about 0.40 in mass fraction . Their conclusion was consistent with the theoretical relationship between the viscosity and solid fraction of the slurry reported by Graham et al The addition of an inhibitor of hydrate formation, such as a surfactant, is effective in suppressing the viscosity of a slurry. Most recently, it was found that adding amino acids to a hydrate slurry reduces its viscosity, thereby reducing the pumping power consumption . Although representative surfactants such as sodium dodecyl sulfate and Span 80, which are not encapsulated in hydrate cages, serve as kinetic promoters for hydrate formation, the phase equilibrium temperature of hydrates undergoes very little change when adding the above surfactants to hydrate formation systems. , Conversely, adding additional guest compounds such as tetrahydropyran alleviate the phase equilibrium conditions …”
Section: Air Conditioningsupporting
confidence: 55%
“…Although TBAB can considerably improve the phase equilibrium conditions for the CO 2 hydrate, the hydrate formed in the TBAB system easily agglomerates and deposits. Therefore, Li et al 165 added an antiagglomeration agent (AA) composed of 90% cocamide propyl dimethyl amine and 10% glycerol to the TBAB solution to improve the hydrate formation. The results indicated that AA can effectively prevent both the agglomeration of the TBAB-CO 2 hydrate and blockage of the separation equipment and improve the gas transfer in the hydrate phase, which considerably increases the hydrate separation efficiency.…”
Section: Other Compound Additivesmentioning
confidence: 99%
“…5 However, agglomeration of CHs is likely to occur in flow lines and industrial apparatus, and is a serious problem to be addressed. 6,7 A promising solution to this problem is injecting low-dosage hydrate inhibitors (LDHIs), which adsorb on a CH surface and interfere with the hydrate agglomeration. 8 To design more effective and environment-friendly synthetic inhibitors than the conventional substances, it is crucial to determine the mechanism of LDHI adsorption on CH surfaces.…”
Section: Introductionmentioning
confidence: 99%